Pengembangan Modul Berbasis Pemecahan Masalah Dalam Pembelajaran Fisika SMA Materi Pemanasan Global - Ninta Sri Ulina (UNIVERSITAS INDRAPRASTA PGRI, 2022)
This study aims to develop a problem-solving-based Physics module in order to complement alternative teaching materials to improve critical thinking skills in high school students. The method used in this research is the development method. Carried out in several stages, namely analysis of the needs of theoretical method developers, validation tests, and field trials. The instruments used are in the form of a needs analysis questionnaire for students and teachers, validation test sheets by high school physics lecturers and teachers and empirical test questionnaire sheets for high school students. The development module is validated by a number of physics material experts, media experts and high school physics teachers who refer to the likert scale. The results of validation by physics material experts obtained data that the modules developed were rated very well with an average score of 83.84%. The validation results by the high school physics teacher, the module was rated very good with an average score of 86.16%. The results of the trial in students stated that the modules developed were rated very well with an average score of 89.49%. Referring to the results of preliminary studies and validation results by high school physics experts and teachers as well as student trials, this study concludes that the problem-solving-based Physics Module in high school physics learning global warming material is suitable for use as alternative teaching materials for the 2013 Curriculum to improve the ability to solve problems in class XI high school students.